2019
DOI: 10.1016/j.ejogrb.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethinyl estradiol-containing oral contraception and other factors on body composition and muscle strength among young healthy females in Finland—A cross-sectional study

Abstract: The aim of this cross-sectional study was to determine the association of hormonal contraception and other life-style factors and habits affecting body composition (BC) and muscle strength. Study design:We measured the body composition of 400 healthy Finnish women (aged 20-40 years) using total body dual energy x-ray absorptiometry (TB-DXA) as well as grip strength (GS [kPa]) with a hand-held dynamometer and knee extension strength (KES [kg]) between 2011 and 2014. Investigated body composition variables were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Only two studies from our search investigated the influence of single hormones on muscle strength and function. One study reported that the dose of synthetic progestogen in OCs did not affect maximal strength (Peters & Burrows, 2006), while another study reported that COC users had less muscle mass and weaker grip strength than females using progestogen‐only OC and non‐users ( n = 141 in COC group, 25 in progestogen group) (Suuronen et al, 2019). This suggests that ethinyl estradiol, but not progestogens, may influence muscle mass and strength in pre‐menopausal females.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies from our search investigated the influence of single hormones on muscle strength and function. One study reported that the dose of synthetic progestogen in OCs did not affect maximal strength (Peters & Burrows, 2006), while another study reported that COC users had less muscle mass and weaker grip strength than females using progestogen‐only OC and non‐users ( n = 141 in COC group, 25 in progestogen group) (Suuronen et al, 2019). This suggests that ethinyl estradiol, but not progestogens, may influence muscle mass and strength in pre‐menopausal females.…”
Section: Resultsmentioning
confidence: 99%
“…However, only healthy volunteers were included, which eliminates the bias due to morbidities. The young reference population has been described earlier in detail 19 . Moreover, the REFERENCE sample may include persons who have completed higher levels of education than the average Finnish population.…”
Section: Discussionmentioning
confidence: 99%
“…During the recruitment REFERENCE population was recruited by stratifying it by age as follows: (20-25 years: n=100, 25-30 years: n=100, 30-35 years: n=100, 35-40 years: n=100). In the REFERENCE population, 11.8% exercised once a week or less, 42% 2-3 times per week, 37.5% 4-6 times per week, and 8.8% daily 19 . No chronic diseases were allowed in the participants for the REFERENCE sample.…”
Section: Young Reference Population (Reference)mentioning
confidence: 99%
See 1 more Smart Citation